A Community-Based Intervention Reduces Diabetes Risk in a Low-Income Community. (29th May 2020) - Ali, Jeneen; Brown, Shavonnea; Guindon, Arlene; Mills, Sarah; Beavers, Alyssa; Shopinski, Samuel; Cress, Diane
Abstract: Objectives: Promote diabetes prevention in low-income communities by offering Cooking Matters TM (CM) in coordination with the Diabetes Prevention Program (DPP). Reducing food insecurity is necessary for reducing chronic disease rates. DPP is a validated and effective intervention for reducing progression to Type II diabetes, but significant outcome disparities occur in low-income communities. Our research aims to address these outcome disparities. This study is a partnership between Gleaners Community Food Bank (GCFB), National Kidney Foundation of Michigan (NKFM), and Wayne State University. DPP, administered by NKFM, is a community-based intervention that significantly reduces diabetes risk. CM, locally administered through GCFB, is also an effective community program that teaches food skills, and provides food provisions. We hypothesize that combining DPP and CM in a low-income setting will improve program completion, and effectively reduce risk for progressing to Type 2 diabetes. Methods: Over 12 months, low-income individuals participated in the combined DPP/CM study. Demographics were collected at the onset of the study. Survey information was collected for diet and physical activity at four time-points throughout the study. Body weight was collected at every session, and HbA1C was collected at the onset and conclusion of the program. Results: Combining DPP and CM resulted in a 79% program completion rate. Mean HbA1C dropped 10.6% (paired t-test, P  < 0.01), and each participant demonstrated lower post-test HbA1C values. Participants experienced a mean weight loss of 7.6% (paired t-test, P  < 0.01), and >75% of participants exceeded the 5% DPP weight loss outcome objective at 12 months. Conclusions: Cooking Matters TM coupled with the Diabetes Prevention Program is an effective strategy to improve outcomes and reduce diabetes risk in low-income communities. Food bank resources can be coupled with existing chronic illness prevention programs to improve both disease risk and food security. Funding Sources: Gleaners Community Food Bank and National Kidney Foundation of Michigan provided funding for this study.